Strategi Imperatif Verbal Guru Dalam Penanaman Nilai Karakter pada Siswa SMA Unggulan di Malang - Sudjalil Sudjalil; Gigit Mujianto (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2017)
This study aimed at1) describing the form, function and meaning of teachers’imperative verbal speech to instill character values on pre, main, and post activities in teaching and learning activities at reputable senior high school students in Malang and 2) describing a model of teachers' verbal imperative strategy in instilling character values at reputable senior high school students in Malang. This study wass classified as descriptive qualitative research. This study based on pragmatic theories especially imperative speech act and character educationtheory teachers’ imperative verbal speech of SMA 3 and SMA Negeri 5 Malang was the data of this study. The data of this study was gained through observation and recording techniques. The data was analyzed by using interactive models techniques by Mills and Huberman. The result of the study showed that: 1) the form of imperative speech used in pre, main, and post activities in teaching and learning activities was formal. Generally, this form enabled to give an instruction to students. Teachers’imperative verbal speech in instilling the character value was meant to give orders, errand, demand, insistence, calling out, allows, invitation, permits, prohibitions, and hope. 2) model of teachers’imperative verbal strategies in instilling the character value was direct imperative strategy and positive politeness strategy. Character values instilled by teacher to student whether on pre, main, and post activities in teaching and learning activities were discipline, honesty, tolerance, hard work, creative, love reading, recognize excellence, open, and friendlyvalues